Comparative architectures of mammalian and chicken genomes reveal highly variable rates of genomic rearrangements across different lineages - Bourque, Guillaume; Zdobnov, Evgeny M.; Bork, Peer; Pevzner, Pavel A.; Tesler, Glenn (Genome Research, 2005)
Molecular evolution studies are usually based on the analysis of individual genes and thus reflect only small-range variations in genomic sequences. A complementary approach is to study the evolutionary history of rearrangements in entire genomes based on the analysis of gene orders. The progress in whole genome sequencing provides an unprecedented level of detailed sequence data to infer genome rearrangements through comparative approaches. The comparative analysis of recently sequenced rodent genomes with the human genome revealed evidence for a larger number of rearrangements than previously thought and led to the reconstruction of the putative genomic architecture of the murid rodent ancestor, while the architecture of the ancestral mammalian genome and the rate of rearrangements in the human lineage remained unknown. Sequencing the chicken genome provides an opportunity to reconstruct the architecture of the ancestral mammalian genome by using chicken as an outgroup. Our analysis reveals a very low rate of rearrangements and, in particular, interchromosomal rearrangements in chicken, in the early mammalian ancestor, or in both. The suggested number of interchromosomal rearrangements between the mammalian ancestor and chicken, during an estimated 500 million years of evolution, only slightly exceeds the number of interchromosomal rearrangements that happened in the mouse lineage, over the course of about 87 million years.